Program Relawan Mengajar Pasca Gempa Bumi Kabupaten Cianjur Pada Bidang Literasi dan Numerasi - Ari Septian; Inayah, Sarah; Aprilla Adawiyah; Aan Hasanah; Elis Homsini Maolida; Asep Saepulloh (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
Literacy and numeracy are considered important and determined as competencies that must be possessed by students. However, the literacy and numeracy competencies of Indonesian students are still low. On the other hand, there is the Covid-19 pandemic which has an impact on the occurrence of a learning crisis. When efforts to improve conditions were about to begin, several areas in Cianjur district experienced an earthquake. One of the areas affected by the earthquake was in Giriharja Village, Cibulakan Village, Cugenang District, Cianjur Regency. An emergency school was set up in the area in the form of a tent erected on a paddy field. FKIP Suryakancana University was called upon to form a teaching volunteer team. The teaching volunteer program aims to raise the enthusiasm of students affected by the disaster to continue learning under any circumstances. This program is also implemented as an effort to deal with traumatic symptoms resulting from the disaster. Through observation, analysis of needs, preparation of lesson plans, learning practices and evaluations, the results were as expected, namely the enthusiasm for learning students revived. The awakening of enthusiasm in students is the initial capital to develop the expected competencies, namely related to literacy and numeracy abilities.